Relaxation and Thermal Conductivity of Hot and Thermal Quasiparticles and Fermi Liquid Interactions in d-wave Superconductors - H. Rabani (Journal of Sciences, Islamic Republic of Iran)
In this paper, we calculate theoretically the relaxation rates of hot, thermal and antinodal quasiparticles by using Fermi’s golden rule. The transition probabilities at low temperatures express in terms of Bogoliubov coefficients, singlet and triplet scattering amplitudes and dimensionless Landau parameters. The values of Landau parameters may be determined by comparison with the experimental data. Furthermore, we calculate thermal conductivity coefficients of YBCO in terms of antinodal quasiparticle relaxation rates which are in accordance with experimental results.